2008
DOI: 10.1071/en08055
|View full text |Cite
|
Sign up to set email alerts
|

Ice nucleation activity of bacteria isolated from snow compared with organic and inorganic substrates

Abstract: Environmental context. Biological ice nucleators have been found to freeze water at very warm temperatures. The potential of bio-aerosols to greatly influence cloud chemistry and microphysics is becoming increasingly apparent, yet detailed knowledge of their actual role in atmospheric processes is lacking. The formation of ice in the atmosphere has significant local, regional and global influence, ranging from precipitation to cloud nucleation and thus climate. Ice nucleation tests on bacteria isolated from sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 47 publications
2
48
1
1
Order By: Relevance
“…For the samples with PS concentrations less than 10 3 CFU/mL, the PS cells tend to be less than 10 for each droplet so that such droplets show less active. These results are not consistent with those reported by Mortazavi et al (2008). They showed that the low concentrations between 10 4 cells/mL and 10 2 cells/mL can also initiate droplet glaciations processes at temperature above -10°C (see Fig.…”
Section: Ice Nucleation Activity Of Bacteriacontrasting
confidence: 56%
See 2 more Smart Citations
“…For the samples with PS concentrations less than 10 3 CFU/mL, the PS cells tend to be less than 10 for each droplet so that such droplets show less active. These results are not consistent with those reported by Mortazavi et al (2008). They showed that the low concentrations between 10 4 cells/mL and 10 2 cells/mL can also initiate droplet glaciations processes at temperature above -10°C (see Fig.…”
Section: Ice Nucleation Activity Of Bacteriacontrasting
confidence: 56%
“…They showed that the low concentrations between 10 4 cells/mL and 10 2 cells/mL can also initiate droplet glaciations processes at temperature above -10°C (see Fig. 5, Mortazavi et al (2008)). We still cannot clearly figure out reasons for those different results.…”
Section: Ice Nucleation Activity Of Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Species with intermediate IN activity begin ice nucleation only at lower temperatures (e.g. Mortazavi et al, 2008). A number of fungi (both free living and lichen fungi) were found to nucleate ice at temperatures comparable to INA bacteria (Table 6), some even at (18C.…”
Section: Pbap As Ice Nucleimentioning
confidence: 99%
“…Mineral dust is considered one of the most efficient ice forming nuclei, partly due to its abundance in global atmospheric aerosols. Certain marine-, vegetation-, and soil-derived aerosols, bacteria, fungi, and their fragments also efficiently nucleate ice (Bigg and Leck 2001;Fröhlich-Nowoisky et al 2014;Georgakopoulos et al 2009;Mortazavi et al 2014aMortazavi et al , b, 2015Mortazavi et al 2008;Schnell and Vali 1976;Vali et al 1976). Recently, research pointed to ice nucleating activity of nanosized organic compounds, possibly peptides, as well as nanosized inorganic compounds such as metal oxides .…”
Section: Introductionmentioning
confidence: 99%